Metodologias [altern]ativas de ensino-aprendizagem no processo de formação do administrador público - Andrade, Donilce Alves de (2018)
Although the technological and teaching advances that are nowadays to everybody disposal, the academic education keep following a traditional way, just limiting the student’s autonomy and does not allow some space for a critical qualification based on a freedom for the teachinglearning process. Active teaching-learning methods brings this autonomy concept, putting teachers and students in a mutual relationship focused on the knowledge search, being both responsible for its building but with the student as the classroom protagonist. As these active teaching-learning methods are most common in the health, engineer, law and business administration areas, this study pretends to do an application proposal from this methods to the Public Administration graduation course, allowing to bring students closer to their professional environment at the public field that presents adversities and changes quickly, according to the national politics and economic situation. To present a better understanding about human and public manager qualification process and about active teaching-learning methods, a bibliographic research was conducted and it results in a referential about autonomy, meaningful and experiential learning process concepts, shows some active teaching-learning methods concepts and results, and presents a short public manager qualification historical context in Brazil. In addition, this study realized an empirical research through focus groups and interview techniques with students and teachers from Public Administration graduation course from a high education institution located in the southern part of the state of Minas Gerais. As a result, it was possible to obtain the student’s perception about a distance between the most used learning methods and the professional practice that they will experience in the future as a public manager. Furthermore, the students also have the comprehension that, even though they find that active methods cause strangeness at the moment the teachers use it, it’s possible to learn the course content in a participative way in the classroom and be more closer from practice. Based on the teacher’s perception, it was possible to obtain the result from a maintenance of some learning methods that does not give the possibility for a bigger student’s participation on the teaching-learning process as a way to be more closer from the professional reality. Some professors demonstrated familiarity with some active teaching-learning methods, but the majority don’t have knowledge about this issue and shows interest in using these methods working together with the expositive class, because they understand this expositive class as a still crucial teaching-learning method. This result just gave the motivation to create this research technical product, that it’s present as a teacher’s guide with some using results from the active teaching-learning methods most used in different areas, giving subsidies to the teacher’s work at the classrooms to build more participative practices.